(untitled) (Geologica Macedonica, 2014)
In this paper the results of micropaleontological research of foraminifer fauna in Paleogene sediments from sections Rabrovo and Dedeli in Valandovo-Gevgelia basin, stratigraphically important for determining Paleogene complex in the basin, are presented. Faunal material were represented by benthic and planktonic foraminiferal fauna and 14 species belonging to 12 genera and 9 families were determined. Key words benthos and planktonic foraminifera; Paleogene sediments; Valandovo–Gevgelia basin